Proceedings of the 2nd International Scientific Conference: »Teaching Methods for Economics and Business Sciences« - Marina Bajić; Gajšt, Nataša; Plos, Alenka (2019)
Besides delivering scientific and professional content, teaching entails fostering students’ learning by adopting effective instructional strategies in an engaging and motivating environment, which needs to be aligned with our intended outcomes and with our varied and specific teaching and learning contexts. These proceedings bring a selection of papers presented at the 2nd International Scientific Conference »Teaching Methods for Economics and Business Sciences« held on 7 May 2018 at the University of Maribor, Faculty of Economics and Business. The authors who submitted their work for this publication share a common interest both in a continuous improvement of their teaching and in the enhancement of their students’ engagement and learning in order to contribute to global prosperity.
Keywords: teaching methods; economics and business; didactics; higher education; students